Restorative Justice Approach on The Under Age (Minors) Violator of The Traffic Case Accident (Laka) That Lead to Death in Polres Majalengka - Malik AL-Ghazali (Jurnal Daulat Hukum, 2018)
The research is qualitative research in the form of descriptive analysis using sociological juridical approach. Types and sources of data used are primary data and secondary data. Data collected through the study of literature and interviews, while the juridical analysis using qualitative analysis. The approach used for the treatment of children in conflict with the law based on values, principles and norms. Pure approach puts the welfare and well-being approach to legal intervention. The punishment model approach to restorative justice called today considered more feasible. For the sake of freedom and rights of the child (fundamental rights and freedom of children) as well as the various interests related to the welfare of children. A limiting factor in the application of Restorative Justice against children in violation of the Act Traffic is due to the factor of legislation often misinterpretation, the factor of law enforcement is the lack of knowledge and skills of investigators in solving criminal cases traffic, factors of infrastructure, a factor of society who do not know information about Restorative justice, Cultural factors personal character actors and victims and their families who do not support the case outside of court settlement or peace. Efforts of traffic guards to avoid conflicts / complaints by victims neutral officer, the offender is directed to the relationship and extend our condolences to the victims, conduct deliberations and request assistance from the Institute of Corrections.Keywords: Restorative Justice; Traffic Accident; Child Actors.